1999
DOI: 10.1038/sj.ejhg.5200383
|View full text |Cite
|
Sign up to set email alerts
|

Genes homologous to the autosomal dominant polycystic kidney disease genes (PKD1 and PKD2)

Abstract: Autosomal Dominant Polycystic Kidney Disease (ADPKD), a common inherited disease leading to progressive renal failure, can be caused by a mutation in either the PKD1 or PKD2 gene. Both genes encode for putative transmembrane proteins, polycystin-1 and polycystin-2, which show significant homology to each other and are believed to interact at their carboxy termini. To identify genes that code for related proteins we searched for homologous sequences in several databases and identified one partial cDNA and two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…Both PCL and PC2 have been found to display highly similar channel properties (20,34). Other highly homologous PKD2 gene homologs have been identified, for which there is no apparent link between their expression and ADPKD (89,126). However, it is possible that their homology to the PKD2 and PKDL genes reflects sensory functions based on their intrinsic channel properties, yet to be determined.…”
Section: The Pc2 Proteinmentioning
confidence: 99%
“…Both PCL and PC2 have been found to display highly similar channel properties (20,34). Other highly homologous PKD2 gene homologs have been identified, for which there is no apparent link between their expression and ADPKD (89,126). However, it is possible that their homology to the PKD2 and PKDL genes reflects sensory functions based on their intrinsic channel properties, yet to be determined.…”
Section: The Pc2 Proteinmentioning
confidence: 99%
“…Meanwhile it could be demonstrated that PKD1 and PKD2 interact with each other through their COOH termini (6,7), indicating that both proteins are part of the same protein complex or signal transduction pathway. The picture becomes even more complex by the recent identification of two PKD2-related proteins, the first of which has been named PKD2L (8,9) and PKDL (10), the second PKD2L2 (9). The genomic location of the genes coding for PKD2L and PKD2L2 makes it unlikely that one of them is involved in renal cyst formation.…”
mentioning
confidence: 99%
“…TRPP proteins have a large extracellular loop located between the first and the second transmembrane domains (S1-S2 loop), which has 224 amino acids in human TRPP2 (5). As a significant portion of TRPP proteins, S1-S2 loops span 23% (in TRPP2), 23% (in TRPP3), or 37% (in TRPP5) of the total protein length (5,35,36). As for the PKD proteins, besides the long extracellular N terminus (Ͼ3000 amino acids in human PKD1), they all have a relatively large extracellular loop between the sixth and seventh transmembrane domains (S6-S7 loop), which is composed of 211 amino acids in human PKD1 (7,8).…”
mentioning
confidence: 99%